MONITORING PEMBACAAN TIMER DAN SUHU MOTOR PADA CENTRIFUGE BERBASIS ARDUINO AT MEGA16 - Abdillah, Khairil; Situmorang, Harold; Siregar, Roni Rahmad (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2023)
Centrifuge is a tool used to separate the liquid according to specific gravity, this tool is used in the laboratory to separate samples such as blood, urine, and others. The main component of Centrifuge is an DC motor that serves to rotate the sample with centrifugal force with the density and time specified. Centrifuge that the author made using microcontroller At Mega 328p and consists of DC motor components, motor drivers, 20x4 lcd, speed sensor, buzzer and keypad. Sensors used are optocoupler sensors that function to determine the speed of the motor, motor drivers are used to adjust the speed of the motor according to the wishes of the user, LCD function to display the speed of the motor and timer, buzzer will sound when the process of separation of the sample has been completed, keypad as input speed, timer and also check the temperature on the motor. Centrifuge is using blood samples, On the motor there are sensors used to determine the speed of the motor. When the speed has been reached, the motor driver will work to control the motor to stay in accordance with the desired speed.